2020
DOI: 10.1002/kjm2.12266
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated METTL3 in nasopharyngeal carcinoma enhances the motility of cancer cells

Abstract: The roles of RNA m6A modification in carcinogenesis have attracted much interest recently. However, the dysregulation of RNA m6A regulators (writers, readers, and erasers) in nasopharyngeal carcinoma (NPC) has never been reported. In this study, we showed that METTL3, one of the writers, was upregulated in NPC. Functional studies revealed that METTL3 promoted the migration and invasion of NPC cells. However, METTL3 knockdown reversed this effect and inhibited the migration, invasion and metastasis of NPC cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…The most recognized underlying mechanism of m6A modification in cancers is that the methylation process of m6A modification is regulated by methyltransferase 13 . METTL3, as the first reported m6A writer, is a major methyltransferase, and its expression is up‐regulated in different cancers such as gastric cancer, nasopharyngeal carcinoma, cervical cancer and liver cancer 35‐38 . In the current research, highly expressed METTL3 was further confirmed in DLBC, CHOL, THYM and liver cancer, and the level of METTL3 was determined to be negatively correlated with the overall survival.…”
Section: Discussionsupporting
confidence: 50%
“…The most recognized underlying mechanism of m6A modification in cancers is that the methylation process of m6A modification is regulated by methyltransferase 13 . METTL3, as the first reported m6A writer, is a major methyltransferase, and its expression is up‐regulated in different cancers such as gastric cancer, nasopharyngeal carcinoma, cervical cancer and liver cancer 35‐38 . In the current research, highly expressed METTL3 was further confirmed in DLBC, CHOL, THYM and liver cancer, and the level of METTL3 was determined to be negatively correlated with the overall survival.…”
Section: Discussionsupporting
confidence: 50%
“…e m6A regulated the metastasis of cancers. METTL3 is upregulated in most tumors, including nasopharyngeal [49], gastric [50], liver [51], and bladder cancers [52], but it is downregulated in colorectal cancer [53].…”
Section: M6a Modification and Metastasismentioning
confidence: 99%
“…The m6A regulated the metastasis of cancers. METTL3 is upregulated in most tumors, including nasopharyngeal [ 49 ], gastric [ 50 ], liver [ 51 ], and bladder cancers [ 52 ], but it is downregulated in colorectal cancer [ 53 ]. The differential expression of METTL3 among tumors plays a dual role, which may reflect differences in targeting pathways and tumor heterogeneity.…”
Section: M6a Modification and Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…As we expected, depletion of METTL3 impaired the OS cell abilities to migrate and invade, and most importantly, curbed the EMT process, one important step for cancer cell metastasis. In nasopharyngeal carcinoma cells, downregulation of METTL3 inhibited the expression of EMT markers Vimentin and N-cadherin [21] . Deletion of METTL3 has been previously found to downregulate m6A and to inhibit the migration, invasion and EMT of cancer cells via regulating Snail and JUNB, both major transcription factors of EMT [22] , [23] .…”
Section: Discussionmentioning
confidence: 97%